Analysis Of Consumer Purchase Decision Towards Collaborative Packaging Design Products Of Dear Me Beauty And KFC - Siti Masrika; Dini Faisal (Institut Nalanda, 2023)
This research aims to determine the influence of packaging design variables from the collaboration between Dear Me Beauty and KFC on consumer purchasing decisions. Respondents for this study were selected using purposive sampling technique, where the respondents were consumers who purchased and used products resulting from the collaboration between Dear Me Beauty and KFC. A total of 84 respondents were included in the research sample. The data collection method employed in this study involved using a Likert-scale questionnaire. The variables studied in this research are collaborative packaging design (as variable X) and purchasing decisions (as variable Y). This study adopts a quantitative approach, and the questionnaire data are analyzed using descriptive statistics.